Phylogeny of certain members of Hyrcanus group (Diptera: Culicidae) in China based on mitochondrial genome fragments - Hui-Min Zhu; Shu-Han Luo; Man Gao; Feng Tao; Jing-Peng Gao; Han-Ming Chen; Xiang-Yu Li; Heng Peng; Ya-Jun Ma (Infectious Diseases of Poverty, 2019)
Abstract Background Species of the Anopheles hyrcanus group are widely distributed in Palearctic and Oriental regions and some of them are important malaria vectors. The cryptic species of An. hyrcanus group was almost impossible to identify based only on their morphology. The phylogenetic relationship of An. hyrcanus group was also not clear. Methods Five members of An. hyrcanus group were identified by rDNA ITS2 sequencing as An. yatsushiroensis, An. belenrae, An. kleini, An. lesteri and An. sineroides. The mitochondrial genome fragments were sequenced and annotated using the mitochondrial genome of An. sinensis as reference. Based on the four segments and Joint Data sequences of these species, and other four anopheline species downloaded from GenBank, intraspecific as well as interspecific genetic distances were calculated and the phylogenetic trees were reconstructed by the methods of neighbor joining, maximum parsimony, minimum evolution and maximum likelihood. Findings Four parts of mitochondrial genomes, which were partial fragments COI + tRNA + COII (F5), ATP6 + COIII(F7 + F8), ND1(F19) and lrRNA (F21), were obtained. All fragments were connected as one sequence (referred as Joint Data), which had a total length of 3393 bp. All fragment sequences were highly conservative within species, with the maximum p distance (0.026) calculated by F19 of An. belenrae. The pairwise interspecific p distance calculated by each fragment showed minor or even no difference among An. sinensis, An. kleini and An. belenrae. However, interspecific p distances calculated by the Joint Data sequence ranged from 0.004 (An. belenrae vs An. kleini) to 0.089 (An. sineroides vs An. minimus), and the p distances of the six members of An. hyrcanus group were all less than 0.029. The phylogenetic tree showed two major clades: all subgenus Anopheles species (including six members of An. hyrcanus group, An. atroparvus and An. quadrimaculatus A) and subgenus Cellia (including An. dirus and An. minimus). The An. hyrcanus group was divided into two clusters as ((An. lesteri, An. sineroides) An. yatsushiroensis) and ((An. belenrae, An. sinensis) An. kleini)). Conclusions The An. hyrcanus group in this study could be divided into two clusters, in one of which An. belenrae, An. sinensis and An. kleini were most closely related. More molecular markers would make greater contribution to phylogenetic analysis.